La virtud odontológica - Flórez-R., Jorge Alejandro (Revista Facultad de Odontología Universidad de Antioquia, 2009)
There is a deeper relationship beetwen ethic and dentistry that is not ussually seen. Dentistry in its technical, therapeutic and interventional aspect is a practical discipline as it is ethics, although directed to diferent objectives. For both, as for any human activity there is a virtue, an excelence in its execution. The dentist must search for this virtue in every activity he/she perfoms in his profession.